Amazon and the German Parcel Market: Stimulus for Competition or Risk of Leveraging? - Stefan Bulowski; Jürgen Kühling; Oliver Zierke (Wirtschaftsdienst)
Abstract Amazon is the largest online marketplace operator in Germany. It also offers logistics services for online retailers and is one of the largest parcel carriers. Its position as an online marketplace operator gives Amazon the opportunity to combine its parcel and logistics services with advantages in its marketplace. Indeed, it may be able to leverage the market power it has in the online marketplace sector in the parcel and logistics markets. Recently, the European Commission requested a commitment from Amazon to prevent undue favouritism towards, among others, marketplace sellers that use Amazon’s logistics and delivery services. It remains to be seen to what extent further interventions will be required.